Digital Extension of Digital Literacy Competence for Islamic Religious Education Teachers in the Era of Digital Learning - Reksiana; Abuddin Nata; Dede Rosyada; Maila Dinia Husni Rahiem; Abdulbosit R. Rafikjon Ugli (Jurnal Pendidikan Agama Islam, 2024)
Purpose –This study aims to analyze the digital literacy competence of Islamic Education teachers at Al-Fath Cirendeu Junior High School, South Tangerang City State Junior High School 3, South Tangerang State Junior High School 6, and Darussalam Ciputat Junior High School. Design/methods/approach – This study used the phenomenological qualitative research method. Research data was obtained through interviews, observations, and documentation studies. The participants in the study were eight Islamic Education teachers and four principals at Al-Fath Cirendeu Middle School, South Tangerang State Middle School 3, Darussalam Ciputat Middle School, and South Tangerang State Middle School 6. The data analysis used in this study was Saldana's Thematic Analysis. Findings – The finding of this dissertation is that the digital literacy competence of PAI teachers in four schools is still at the level of simple learning media users. The data in this study shows that the application of the digital literacy competence of PAI teachers is limited to ICT media users such as YouTube, PPT, Quizizz, Google Classroom, and Google Form which are used as learning media for preparation, delivering material, and learning assessment. Meanwhile, the creation of digital teaching materials has not been able to be done. Research implications/limitations – Practically, the results of the dissertation can provide input to Islamic Education teachers in four schools and Islamic Education teachers, practitioners and education policy makers (government) regarding the implementation of digital literacy competencies in learning and in developing a digital literacy competency model in learning that leads to sustainable curriculum development.